Upaya Peningkatan Kualitas Pengelolaan Pendidikan Melalui Pengembangan Manajemen Sumber Daya Manusia - Dewi Yanti (Departement of Mathematics Education, 2023)
The purpose of this study is to examine further the Efforts to Improve the Quality of Islamic Education Management through the Development of Human Resource Management. This work was written based on a literature review and in-depth understanding and accumulated understanding from various trusted primary book sources. This type of research is qualitative with a library research approach. Data collection techniques are carried out with documentation. Sources of data come from books and journals. The data analysis technique uses content analysis. The results of the study show that every educational institution that wants to progress and develop must pay attention to its human resources and manage them properly and realize quality and quality education. Human resource development means that there is a process of planning, organizing, directing, and controlling as a management function in general. The development of human resources can also be seen from the process of procuring or funding human beings, the compensation provided, the integration between one element and another, and the existence of maintenance in order to achieve the goals of educational institutions in Islamic educational institutions, quality human beings. resources when viewed from an Islamic point of view that the management of human resources in Islamic educational institutions must refer to what has been exemplified by the Prophet Muhammad SAW.